Implementation of a Forward Chaining Method for Lupus Detection in RSUD Jayapura City - Nurul Aprilianti, Ratih; Pawan, Elvis; Irjanto, Nourman S. (MultiTech Publisher, 2024)
Implementation of expert system for lupus disease detection at RSUD Jayapura City achieved 100% in functionality testing of 8 forms, showing a high degree of accuracy. The benefits include ease of diagnosis for medical officers and access to information for the public. Integration with Android platforms and forward chaining methods improves diagnostic accuracy, expands use, and increases effectiveness in early identification of lupus disease. This success demonstrates the enormous potential of technology in improving health care and the quality of life of the people.